Long-term monitoring for short/branched-chain acyl-CoA dehydrogenase deficiency: A single-center 4-year experience and open issues - Rossi, Alessandro; Turturo, Mariagrazia; Albano, Lucia; Fecarotta, Simona; Barretta, Ferdinando; Crisci, Daniela; Gallo, Giovanna; Perfetto, Rosa; Uomo, Fabiana; Vallone, Fabiana; Villani, Guglielmo; Strisciuglio, Pietro; et al. (Frontiers in Pediatrics, 2022)
Introduction: Short/branched-chain acyl-CoA dehydrogenase deficiency (SBCADD) is an inherited disorder of L-isoleucine metabolism due to mutations in the ACADSB gene. The role of current diagnostic biomarkers [i.e., blood 2-methylbutyrylcarnitine (C5) and urine 2-methylbutyrylglycine (2MBG)] in patient monitoring and the effects of proposed treatments remain uncertain as follow-data are lacking. This study presents first systematic longitudinal biochemical assessment in SBCADD patients. Methods: A retrospective, observational single-center study was conducted on newborns born between 2017-2020 and suspected with SBCADD. Biochemical, molecular, clinical and dietary data collected upon NBS recall and during the subsequent follow-up were recorded. Results: All enrolled subjects (n=10) received adequate protein intake and carnitine supplementation. Nine subjects were diagnosed with SBCADD. During the follow-up [median: 15 (4-30) months] no patient developed symptoms related to SBCADD. No patient normalized serum C5 and urine 2MBG values. In 7/9 SBCADD patients mean serum C5 values decreased or stabilized compared to their first serum C5 value. A major increase in serum C5 values was observed in two patients after carnitine discontinuation and during intercurrent illness, respectively. Urine 2MBG values showed moderate intra-patient variability. Discussion: The relatively stable serum C5 values observed during carnitine supplementation together with C5 increase occurring upon carnitine discontinuation/intercurrent illness support the value of serum C5 as a monitoring biomarker and the benefit of this treatment in SBCADD patients. The role of urine 2MBG in patient monitoring remains uncertain. As all patients were asymptomatic, no association between biochemical parameters and clinical phenotype could be investigated in this study.